Study of Accidental Death Due to Road Traffic Accidental Cases Recorded at Forensic Medicine Department of Dinajpur Medical College, Dinajpur (Bangladesh Journal of Medicine, 2013)
Bangladesh Journal of Medicine, Vol 23 No 2, 2012, Page 50-51 DOI: http://dx.doi.org/10.3329/bjmed.v23i2.14983